2007
DOI: 10.1002/pmic.200700612
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of matrix vesicles isolated from femurs of chicken embryo

Abstract: Matrix vesicles (MVs) are extracellular organelles that initiate mineral formation, accumulating inorganic phosphate (P(i)) and calcium leading to the formation of hydroxyapatite (HA) crystals, the main mineral component of bones. MVs are produced during bone formation, as well as during the endochondral calcification of cartilage. MVs are released into the extracellular matrix from osseous cells such as osteoblasts and hypertrophic chondrocytes. In this report, using 1-D SDS-PAGE, in-gel tryptic digestion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 90 publications
4
87
0
Order By: Relevance
“…These membrane proteins play a role in the efflux of metabolites including ATP and phosphate in the mitochondria. 40 Interestingly, these proteins are recurrently identified in matrix vesicles (MV), 14,41 the organelles implicated in initiation of mineralization. 41,43 Start of mineral deposition occurs by accommodating the proper environment for crystal growth in the MV.…”
Section: Discussionmentioning
confidence: 99%
“…These membrane proteins play a role in the efflux of metabolites including ATP and phosphate in the mitochondria. 40 Interestingly, these proteins are recurrently identified in matrix vesicles (MV), 14,41 the organelles implicated in initiation of mineralization. 41,43 Start of mineral deposition occurs by accommodating the proper environment for crystal growth in the MV.…”
Section: Discussionmentioning
confidence: 99%
“…Nascent HA crystals exposed to the extravesicular fluid have been found to bind OPN, a collagen-binding molecule (Chen et al 1992;Liu et al 2007;Martin et al 2004). Given that MVs display collagen-binding molecules on their membranes (TNAP, Annexin A5 (AnxA5)) (Balcerzak et al 2008;Wu et al 1991;Xiao et al 2007), it is conceivable that a specific binding of MVs to collagen mediates the physical transfer of HA crystals to the exterior of collagen fibrils. This model does not negate, nor is it incompatible with, data indicating that crystals are able to form in the gaps and holes of the collagen fibrils, as has been well demonstrated by the work of many investigators, but if proven correct it would help explain how crystals formed within MVs can contribute to ECM mineralization.…”
Section: The Role Of Phosphatases In Mv-mediated Initiation Of Skeletmentioning
confidence: 99%
“…Almost 40 years after the existence of the NKA pump was proposed, Hsu and Anderson (1996) described that an ATPase inhibited by vanadate, but not by alkaline phosphatase, could be also responsible for initiating Ca 2+ and P i deposition into intact MVs (Hsu and Anderson 1996). In a study carried out much later on the proteome of the chicken embryo, Balcerzak et al (2008) revealed MVs to be a very complex biological environment where they identified 23 transporter proteins. Among them, five α and β subunits from NKA self-assemble in specific dimers that can subsequently associate into multimeric species (Tokhtaeva et al 2012;Yoneda et al 2016).…”
Section: The Role Of Transporters In Mv-mediated Initiation Of Skeletmentioning
confidence: 99%
See 1 more Smart Citation
“…While progress has been made in the study of MVs, (3,(7)(8)(9)(10). Data on the MVs protein component have been generated.…”
Section: Introductionmentioning
confidence: 99%